2003
DOI: 10.1088/0022-3727/36/7/318
|View full text |Cite
|
Sign up to set email alerts
|

Activation analysis of deformation in evaporated molybdenum thin films

Abstract: Using nanoindentation, we investigate hardening mechanisms in steered arc (SA) evaporated and electron-beam (EB) evaporated molybdenum thin films. Both films have columnar grains, with the column diameters ranging between 22 and 170 nm in the SA films and 30 and 40 nm in the EB films. The Hall-Petch relation is extended out to hardness values between 6 and 12 GPa. Analysis of nanoindentation creep data (creep, load relaxation, and rate change) reveals that, in the SA films, thermally activated glide is rate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Furthermore, the high entropic effect, sluggish diffusion, and lattice distortion in RHEA films contribute to the measured high hardness and Young’s modulus . The hardness of the CuMoTaWV RHEA film is found to be higher than that of refractory metals, such as W, Ta, and Mo thin films with a hardness of 14, 11.6, and 11.8 GPa, respectively. In general, refractory metals are found to be harder than transition metals, such as Ni and Cu, with a hardness of 6.4 and 6 GPa, respectively, due to their strong bonding and crystal structure. , The hardness of CuMoTaWV was found to be even higher than those of previously reported bulk RHEAs, such as TiHfZrTaNb, with a hardness of 4.9 GPa, and RHEA films, such as NbMoTaW, TaNbHfZr, TiTaHfNbZr, and HfNbTiVZr, with a hardness of 16, 15, 12.5, and 9.2 GPa, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, the high entropic effect, sluggish diffusion, and lattice distortion in RHEA films contribute to the measured high hardness and Young’s modulus . The hardness of the CuMoTaWV RHEA film is found to be higher than that of refractory metals, such as W, Ta, and Mo thin films with a hardness of 14, 11.6, and 11.8 GPa, respectively. In general, refractory metals are found to be harder than transition metals, such as Ni and Cu, with a hardness of 6.4 and 6 GPa, respectively, due to their strong bonding and crystal structure. , The hardness of CuMoTaWV was found to be even higher than those of previously reported bulk RHEAs, such as TiHfZrTaNb, with a hardness of 4.9 GPa, and RHEA films, such as NbMoTaW, TaNbHfZr, TiTaHfNbZr, and HfNbTiVZr, with a hardness of 16, 15, 12.5, and 9.2 GPa, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…12 13 Indentation creep has been studied by a number of researchers. [14][15][16][17][18][19][20] The most common method of measuring creep is to maintain the applied force at a constant maximum value and measure the change in depth of the indenter as a function of time. The relative change of the indentation depth is referred to as the "creep" of the specimen material.…”
Section: Nanoindentationmentioning
confidence: 99%
“…By the aid from the grain growth inhibitor like ZrC particles located at the grain boundaries, the creep of the Mo alloy with 0.8 mol% dispersed zirconium carbide (ZrC) and with the 300 nm average grain size under 1500°C indicated the superplasticity behavior ( n = 2.44) . At near ambient temperature, the nanoindentation creep data of Mo thin film (30‐40 nm grain size) showed that the creep exponent was close to 6.67—the value related to the thermally activated glide‐controlled creep …”
Section: Introductionmentioning
confidence: 99%